Psychometric properties of the expanded version of the inventory of depression and anxiety symptoms (IDAS-II) in a sample of older adults. (1st November 2020) - Weitzner, Daniel; Calamia, Matthew; Stasik-O'Brien, Sara M.; De Vito, Alyssa; Pugh, Erika
Abstract: Objective: Given the strong relationship often found between self-report measures of anxiety and depression, the Inventory of Depression and Anxiety Symptoms (IDAS) was created and then expanded (IDAS-II) to assess common and unique symptom dimensions of these emotional disorders. Limited research has focused on the use of the IDAS-II with older adults and the purpose of the current study was to provide data on the reliability and validity of the IDAS-II in this population. Method: A sample of 323 participants (age 55–80 years) were recruited online using Amazon's Mechanical Turk (MTurk). They completed the IDAS-II and several other self-report questionnaires of internalizing symptoms, including widely used measures developed specifically for older adults. Internal consistency and validity of the IDAS-II were examined. Results: The IDAS-II demonstrated marginal to excellent internal consistency ( α = .68–.91). An exploratory factor analysis indicated three factors: Distress, Positive Mood, and Obsessions. The IDAS-II explained a large amount of variance in the other measures of depression and anxiety (ranging from 52% to 76%) and the IDAS-II Dysphoria scale significantly related to all of the other measures of depression and anxiety (ranging from r = .69 to r = .81). Conclusion: These results support the use of the IDAS-II with older adults as it has good convergent validity with other commonly used measures of depression and anxiety, including those commonly used in the assessment of older adults. Further research can use the IDAS-II with both younger and older adults to examine age-related changes in depression and anxiety symptoms.